Having Once Paused : Poems of Zen Master Ikkyu (1394-1481) - Ikkyū, 1394-1481 (Book collections on Project MUSE., 2015)
A volume of selected poems by Zen Master Ikkyu Sojun (1394-1481), translated into English.